Findings of Slovene linguists on the grammatical form of the future tense in the Slovene language - Orožen, Martina (Slavia Centralis, 2021)
The discussion presents the views of Slovene linguists (Valentin Vodnik, Jernej Kopitar, Fran Metelko, Ivan Navratil, Franc Miklošič, Janez Šolar, Anton Janežič, Stanislav Škrabec, Viktor Bežek) on the use of the future tense in the Slovene language of the 18th and 19th centuries. All questions regarding futural and modal possibilities of expression in the Slovene literary language have not been comprehensively addressed, so it is necessary to explain the development of oppositions to futural and modal forms in the historical development of literary Slovene language and treat them hierarchically as (1) a futural grammatical form, (2) a perfect present tense, and (3) modal and other indefinite conjunctions.